2021
DOI: 10.1088/1361-6463/abcdd1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric dielectric barrier discharge containing helium–air mixtures: the effect of dry air impurities on the spatial discharge behavior

Abstract: Air is a typical and arguably unavoidable impurity in atmospheric pressure dielectric barrier discharges (DBDs). The introduction of air may bring rich plasma chemical effects on DBDs and lead to a significant change of discharge characteristics. Here we implement a two-dimensional fluid model to study the spatial discharge behavior in a helium–dry-air DBD under the air impurity level (N air) of 10–200 ppm. The simulation results reveal that under low impurity content (less than 30 ppm), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…The current plasma modeling literature focuses on plasma breakdown in the absence of a structure being treated [40][41][42][43][44][45][46][47]49] . When a porous structure is modeled inside of a plasma-containing vessel [57][58][59] , the computational cost associated with plasma modeling limits researchers to modeling a small fraction of the complex structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current plasma modeling literature focuses on plasma breakdown in the absence of a structure being treated [40][41][42][43][44][45][46][47]49] . When a porous structure is modeled inside of a plasma-containing vessel [57][58][59] , the computational cost associated with plasma modeling limits researchers to modeling a small fraction of the complex structure.…”
Section: Discussionmentioning
confidence: 99%
“…[46,47] The development of the COMSOL Multiphysics® plasma module leads to the deployment of 2D axisymmetric full plasma models. [48,49] However, previous works model plasma inside an otherwise empty vessel or flowing around simple structures. Modeling a full nitrogen plasma, which is commonly used in surface engineering, continues to be a computational challenge due to the number of chemical reactions involved.…”
Section: Introductionmentioning
confidence: 99%
“…The second parameter responsible for the filamentary/ homogeneous behavior is seed electron density (n seed ). Cold atmospheric plasmas generated in dielectric barrier devices supplied with argon or helium commonly have a background of ambient air, i.e., N 2 and O 2 molecules (typically 10-100 ppm) even after a few minutes of purge (Wang et al, 2021). These socalled contaminants can interact with atoms of noble gas in a metastable state (X m ) and potentially induce Penning reaction as shown in Eq.…”
Section: The Carrier Gas Nature Influenced the Filamentary/homogeneou...mentioning
confidence: 99%
“…The discharge characteristics of unclean air has been studied by scholars at home and abroad [12][13][14][15][16]. Dzlieva and others have studied the effect of dust on the DC breakdown voltage of high-pressure gas.…”
Section: Introductionmentioning
confidence: 99%
“…Ermolenko et al simulated and analysed with the influence of multiphase medium on the electric field of plasma reactor by finite element method, and proposed that water droplets/metal particles in the air gap can seriously distort the surrounding electric field, resulting in the formation of small corona area of air medium [18]. Yi et al found that many haze and haze external insulation discharge accidents in Guangzhou Power Grid include both insulator surface flashover caused by wet settlement and air gap breakdown discharge [10,16]. The air gap discharge is mainly due to the drift dust in the air, that is, the solid particles in the haze ionise the positive and negative ions under appropriate conditions, which reduces the insulation performance of the air medium.…”
Section: Introductionmentioning
confidence: 99%